2020
DOI: 10.3390/pr8030303
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Polymerization Catalytic Process Effect of Various Organic Wastes on Reaction Time, Yield, and Temperature

Abstract: The purpose of this study is to optimize the processing conditions (temperature, pressure, process time, yield rate) for the conversion of biomass to a high-energy density biofuel. The hydrothermal polymerization (HTP) catalytic process has been developed for production of biofuel via hydrothermal processing using an acid-based catalyst. This study has shown that the HTP catalytic process for a reference feedstock lowered the temperature by 10 to 40 • C, reduced the pressure requirement by 1 to 2 MPa, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The choice of synthesis method will depend on the type of pollutant to be degraded or the end-use of the photocatalyst. Based on the literature it can be concluded that chemical methods are mostly used in the preparation of RGO-Bi 2 MoO 6 and among chemical methods, hydrothermal method is very common and it has been proven to produce a more efficient, chemically stable RGO-Bi 2 MoO 6 [51,52].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The choice of synthesis method will depend on the type of pollutant to be degraded or the end-use of the photocatalyst. Based on the literature it can be concluded that chemical methods are mostly used in the preparation of RGO-Bi 2 MoO 6 and among chemical methods, hydrothermal method is very common and it has been proven to produce a more efficient, chemically stable RGO-Bi 2 MoO 6 [51,52].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Their so-called hydrothermal polymerization (HTP) process attained a high energy density of 27 MJ/kg and a mass yield rate of 60%. By using catalysts, the process temperature was lowered by 10 to 40 • C, the pressure requirement was reduced by 1 to 2 MPa, the rate of yield was 22% higher, and the total processing time was shortened by 3 h. These facts tell us the HTP process can use milder and quicker operation conditions with higher energy value and yield rate comparing with other catalytic and non-catalytic HTC reactions for wood biomass [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…They demonstrated a 30% increase of higher heating value (HHV) comparing to a non-catalytic process. Mackintosh et al compared various study results on the catalyst effect on HTC with newly defined efficiency of the catalyst on HTC [12]. They used maleic acid as catalyst and optimized the operating conditions for wood chips: temperature = 220 • C, pressure = 2.3 MPa, process time = 1 h, and the amount of the catalyst = 20 g/L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamics of each AD stage and potential bacterial competitions have been reported in detail by [13,14]. In order to have a balanced AD, identical reaction rates are desired, however, the hydrolysis step is considered to be the rate limiting step for the digestion of lignocellulosic matter due to the impact of high lignin content on mass transfer [5,[15][16][17]. Although the impact of various pre-treatment technologies have been investigated on lignocellulosic materials-such as municipal organic waste [18], wheat straw and sugarcane bagasse [19], maple, oak and corn leaves and stalks [20], maize straw [21], corn stove [22], palm waste [23], lignocellulosic biomass [24], algal biomass [25] with an ultimate goal of achieving lignin solubilisation as well as reducing the crystal structure of cellulose to render readily degradable materials accessible to bacterial attack [26-28]-implementation of pre-treatment on whiskey distillery and brewery wastes and its impact on lignocellulose fractions have received scant attention in the literature [29].Chemical pre-treatment is a well-studied and widely accepted method in AD for a variety of lignocellulosic feedstocks [4,30].…”
mentioning
confidence: 99%